Transgender identities towards a social analysis of gender diversity - Hines, Sally; Sanger, Tam (Routledge research in gender and society, 2010)
"This volume offers vivid accounts of the diversity of living transgender in today's world. The first section, "Emerging Identities," maps the ways in which social, cultural, legal and medical developments shape new identities on both an individual and collective level. Rather than simply reflecting social change, these shifts work to actively construct contemporary identities. The second section, "Trans Governance," examines how law and social policy have responded to contemporary gender shifts. The third section, "Transforming Identity," explores gender and sexual identity practices within cultural and subcultural spaces. The final section, "Transforming Theory?", offers a theoretical reflection on the increasing visibility of trans people in today's society and traces the challenges and the contributions transgender theory has brought to gender theory, queer theory and sociological approaches to identity and citizenship." "Featuring contributions from throughout the world, this volume represents the cutting-edge scholarship in transgender studies and will be of interest to scholars and students interested in gender, sexuality, and sociology."--Book jacket.